Coastal Vulnerability Assessment to Tidal (ROB) Flooding In Indramayu Coast, West Java, Indonesia - Putiamini, Sepanie; Patria, Mufti Petala; Soesilo, Tri Edhi Budhi; Karsidi, Asep (Indonesian Journal of Geography, 2023)
Aquaculture practices in developing countries, particularly Indonesia, are currently operating without effective control measures, leading to high tidal and other climate-related issues. Therefore, this study aimed to modify Coastal Vulnerability Index (CVI) assessment to evaluate the physical vulnerability of coastal areas in Indramayu Regency, West Java (62 sections) to tidal flooding (Rob). A total of 6 primary characteristics, including geomorphology, beach slope, water level rise sea, coastline alterations, tidal range, and high tide, as well as 2 additional parameters, namely land cover and mangrove breadth, were used for analysis. Based on the evaluation, CVI was divided into four groups, including (1) low, (2) moderate, (3) high, and (4) very high. The results showed that Indramayu District struggled to recover from tidal flooding, with 24.56%, 22.13%, 41.03%, and 12.28% being placed in the very high, high, moderate, and low categories. This underscored the role of local governments in improving coastal communities' capacity to respond to tidal flooding disasters. Furthermore, the results were expected to be used by local governments to enhance disaster mitigation systems, particularly for coastal areas in developing nations with comparable ecological conditions.